Analisis Penerimaan dan Penggunaan Aplikasi E-LKP UIN Raden Fatah Palembang Menggunakan Model for Mandatory Use of Software Technologies - Nurdarani Rani; Ruliansyah Ruliansyah; Muhammad Leandry Dalafranka (APTIKOM SUMSEL, 2021)
Electronic Employee Performance Sheet (E-LKP) is a website-based application of the State Islamic University of Raden Fatah Palembang used by ASN employees and lecturers with additional tasks with the aim of reporting their performance results. This study aims to determine the acceptance and use of the E-LKP Application (Electronic-Employee Performance Sheet) at UIN Raden Fatah Palembang using the Model for Mandatory Use of Software Technologies (MMUST) and using all variables in MMUST, namely 8 constructs in the form of Information Quality, Information Satisfaction, Social Influence, Performance Expectancy, Attitude, Use, Overall Satisfaction, and Net Benefits. The data in this study were collected using a questionnaire distributed to 186 respondents. The data analysis used is using PLS-SEM with the Smart-PLS version 3.0 tool. The overall results of this study indicate that the acceptance and use of the E-LKP application at UIN Raden Fatah Palembang using the Mandatory Use of Software Technologies (MMUST) Model has an effect of 92.8%. From this percentage, it can be said that the E-LKP application at UIN Raden Fatah Palembang has been accepted and used by users, namely ASN employees and lecturers with additional assignments.